550 Modified hypoxic challenge testing in children on nocturnal ventilation. (17th August 2022) - Samuels, Martin; Riley, Mollie; Kelly, Paula; Brotherston, Stephanie; Pike, Katharine
Abstract : Aims: Children with neuromuscular and central hypoventilation conditions are living longer, fuller lives which may include air travel. Guidelines for passengers with respiratory disease focus on primary lung pathology and management of hypoxia worsened at altitude. Little data exist to guide professionals advising children at risk of nocturnal hypoventilation. We assessed the response to low ambient oxygen using a modified hypoxic challenge test and how well this was tolerated by our patients. Methods: Twenty children on nocturnal ventilation and with a mean age of 8.7 years (range 1.6 - 18) were studied, 10 with neuromuscular weakness and 10 central hypoventilation. Participants underwent two-stage, modified hypoxic challenge testing in a chamber which could accommodate a wheelchair (see figure 1 ). We measured oxygen saturation (SpO2) and transcutaneous carbon dioxide (tcpCO2) in a conventional stage, where oxygen alone was titrated according to SpO2 and then in a new stage, where participants used their routine ventilatory support with oxygen titrated if needed. Participants were interviewed to understand their experiences of testing and of air travel. Results: In 15% ambient oxygen, a condition simulating flight, 13/20 participants needed supplemental oxygen as a result of falling below threshold (SpO2<90%), but only two did when using ventilatory support. Transcutaneous carbon dioxide remained within normal range for all participants, on or off ventilatory support, but fell by a mean 0.7kPa on ventilation compared to 0.2kPa on O2 alone. Whilst some participants found testing challenging, participants generally reported both testing and air travel to be valuable. Conclusion: Evaluating response to patients' usual ventilation within a 'fitness-to-fly' assessment aids decision making when considering whether children who receive nocturnal ventilation can travel by air, since for some using a ventilator reduces or avoids the need for supplemental oxygen. We have developed a new testing protocol, which works well in children with known hypoventilation (see figure 2 ).